2010
DOI: 10.1111/j.1365-2044.2010.06375.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative vitamin B infusion and prevention of nitrous oxide‐induced homocysteine increase

Abstract: Summary Nitrous oxide inactivates vitamin B12 with detrimental consequences for folate and methionine metabolism. This inactivation can be clinically detected by an increase in plasma total homocysteine. In a clinical trial, we tested the hypothesis that a preoperative infusion of vitamin B12 and folate prevents the nitrous oxide-induced homocysteine increase. Sixty-three healthy patients scheduled for elective surgery were randomly allocated to receive (a) B-vitamins and nitrous oxide; (b) placebo and nitrous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…Second, it has been repeatedly shown in more than 6 human studies (>1,000 patients) that in the absence of N 2 O, patients will not develop an increase in postoperative plasma tHcy. 3,4,14,40-42 Based on these preexisting data, it is a reasonable prediction that we would have observed a similar result (no increase in plasma tHcy without N 2 O), if our study had a formal control group.…”
Section: Discussionsupporting
confidence: 66%
“…Second, it has been repeatedly shown in more than 6 human studies (>1,000 patients) that in the absence of N 2 O, patients will not develop an increase in postoperative plasma tHcy. 3,4,14,40-42 Based on these preexisting data, it is a reasonable prediction that we would have observed a similar result (no increase in plasma tHcy without N 2 O), if our study had a formal control group.…”
Section: Discussionsupporting
confidence: 66%
“…Woodside et al 26 showed the positive significant effect of vitamin B on plasma homocysteine levels in men. In contrast, Rao et al 7 found intravenous injections of vitamin B to be ineffective on hyperhomocysteinemia after nitrous oxide anesthesia. This inconsistency can be explained by the absence of standard techniques of anesthesia and different durations of exposure to nitrous oxide in the mentioned studies.…”
Section: Discussionmentioning
confidence: 90%
“…6 During this period, cobalamin-dependent enzymes, namely methionine synthase are inhibited, the ability of the cells to produce methionine from homocysteine is impaired, and consequently plasma homocysteine level increases. [2][3][4][5][6][7] Since homocysteine has atherogenic properties that can lead to endothelial dysfunction, [8][9][10][11] its higher plasma levels augment the risk of myocardial infarction, stroke, and dementia in the general population, particularly in individuals with cardiovascular risk factors. 12,13 Therefore, the effects of elevated plasma homocysteine levels are very important in cardiac patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çalışmamızdan farklı olarak, Lee ve ark. (13) , yaptıkları çalışmada, remifentanili bolus (1-2 μg kg (15) . Böylece redükte durumdaki kobalaminden okside kobalamin oluşur.…”
Section: Discussionunclassified